Desiccation of potatoes with herbicides - Vranješ, Filip; Đekić, Radomir (Acta herbologica, 2023)
Desiccation is an agro-technical measure that has been present in agricultural practice for many years. Desiccation of potatoes enables better control of tuber size, physiological uniformity, uniformity in crop ripening, standardization of skin color and firmness, minimization of tuber malformations, and reduces the appearance of pathogens and pests, removes weeds and aboveground mass of potatoes for easier harvesting. During the desiccation of potatoes, the above-ground parts can be eliminated by mechanical, mechanical-chemical, or chemical methods. The aim of this research is to determine the effect of different herbicides as potato desiccants if used in the phenological phase of potato ripeness. Herbicides used in this study were based on a.s. diquat, piraflufen-ethyl + mineral oil, piraflufen-ethyl, carfentrazone-ethyl in single and split application. In the last assessment, 11 DAT, the best effect was achieved with a.s. diquat (100%), then with a.s. pyraflufen-ethyl + mineral oil (92%), a.s. pyraflufen-ethyl without adjuvant had a lower effect (81%), a.s. carfentrzon-ethyl in the unilateral application was at a similar level (78%), and the lowest effect had the treatment with a.s. carfentrazone-ethyl in the split application (58%). The results of these studies have shown that carfentrazone-ethyl and pyraflufen-ethyl can be used for potato desiccation, yet farmers must consider their lower efficiency, e.g. slower action compared to a.s. diquat. It is recommended to add an adjuvant to the herbicide in order to improve its effectiveness.